New results in robust functional state estimation using two sliding mode observers in cascade. (3rd March 2013) - Kee, Chew Yee; Tan, Chee Pin; Ng, Kok Yew; Trinh, Hieu
SUMMARY This paper presents a functional observer scheme using two sliding mode observers in cascade. A coordinate transformation is performed on the system such that existing sliding mode observer theory can be directly applied to achieve functional state estimation. The necessary and sufficient existence conditions for the scheme (in terms of the original system matrices) are also investigated, and they are found to be less stringent than earlier work on functional state estimation using one sliding mode observer; this could have benefits in terms of cost and simplicity. A numerical example verifies the effectiveness of the scheme. Copyright © 2013 John Wiley & Sons, Ltd.